1992
DOI: 10.1002/pros.2990200403
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth of PC‐82 human prostate cancer line xenografts in nude mice by bombesin antagonist RC‐3095 or combination of agonist [D‐Trp6]‐luteinizing hormone‐releasing hormone and somatostatin analog RC‐160

Abstract: The effects of treatment with a bombesin receptor antagonist [D-Tpi6, Leu13 psi (CH2NH) Leu14]BN(6-14)(RC-3095) and the combination of an agonist of luteinizing hormone-releasing hormone [D-Trp6]-LH-RH and somatostatin analog D-Phe-Cys-Tyr-D-Trp-Lys-Val- Cys-Trp-NH2 (RC-160) were studied in nude mice bearing xenografts of the hormone-dependent human prostate tumor PC-82. During the 5 weeks of treatment, tumor growth was decreased in all treated groups compared with controls. Bombesin antagonist RC-3095 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 39 publications
3
54
0
Order By: Relevance
“…It has also been demonstrated that bombesin antagonist RC-3095 can effectively inhibit growth of a number of cancers (9,13,15,16). In premalignant lesions induced by DMBA in the hamster buccal cheek pouch, RC-3095 reduced the rate of progression of these lesions toward invasive carcinomas (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that bombesin antagonist RC-3095 can effectively inhibit growth of a number of cancers (9,13,15,16). In premalignant lesions induced by DMBA in the hamster buccal cheek pouch, RC-3095 reduced the rate of progression of these lesions toward invasive carcinomas (10).…”
Section: Discussionmentioning
confidence: 99%
“…One pseudononapeptide bombesin/GRP antagonist, RC-3095 {[D-Tpi6, Leu13-_{CH2NH)-LeuI4]bombesin (6)(7)(8)(9)(10)(11)(12)(13)(14), where Tpi is 2,3, 4,9-tetrahydro-lH-pyridol [3,4-b]indol-3-carboxylic acid}, inhibits amylase release from the rat pancreas (9) and competes effectively for binding with bombesin in small cell lung carcinoma cells H-345 (9). This same antagonist has been found to decrease the progression of carcinogen-induced premalignant lesions (10) and to inhibit the growth of a wide variety of cancers, including MCF-7 MIII (11) human breast cancers, MXT mouse mammary cancers (12), nitrosamineinduced pancreatic cancers in hamsters (13,14), HT-29 colon cancers (15), and PC-82 prostate cancers (16). These results have suggested that some human cancers could respond to treatment with bombesin/GRP antagonists such as RC-3095.…”
mentioning
confidence: 93%
“…Neuroendocrine cells are known to secrete neuropeptides, which are involved in diverse biological processes, including cellular proliferation, transformation, and invasion (74,94). These neuropeptides, exemplified by bombesin and NT, have been shown to be potent in vitro mitogens (73,74) and are implicated in a variety of human malignancies in the lung (31,36,89,90), breast (61,64), and prostate (16,44,51,56). For prostate cancers, it was shown that the receptors for bombesin/gastrin-releasing peptide (GRP) are present in all prostate cancer cell lines examined, including PC3, DU145, and LNCaP (9,13,55), and their expression levels are increased in more-advanced tumor specimens compared to less-advanced tumor specimens (55).…”
mentioning
confidence: 99%
“…Antitumoral effects of BN͞GRP antagonists in vivo have been demonstrated on CFPAC-1 and SW-1990 human pancreatic cancers (17,18), nitrosamine-induced pancreatic cancers in hamsters (19), H69 human SCLC (20), MKN45 and Hs746T human gastric cancers (21,22), HT-29 human colon cancers (23,24), PC-82, PC-3, and DU-145 human prostate cancers (25,26), androgen independent Dunning R-3327-AT-1 rat prostate cancers (27), estrogen dependent and independent MXT mouse mammary cancers (28), MCF-7 MIII human breast cancer (29), and U-87MG and U-373MG human glioblastomas (30). Receptor analyses of these tumors showed the presence of high-affinity binding sites for 125 I[Tyr 4 ]BN (1,2,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Recently, we described the synthesis and evaluation of cytotoxic analogs of luteinizing hormone-releasing hormone containing doxorubicin (DOX) or 2-pyrrolino-DOX, a derivative 500-1000 times more potent (34,35).…”
mentioning
confidence: 99%